Embodied and disembodied technological change: The sectoral patterns of job-creation and job-destruction - Giovanni Dosi; Mariacristina Piva; Maria Enrica Virgillito; Marco Vivarelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
This paper addresses, both theoretically and empirically, the sectoral patterns of job creation and job destruction in order to distinguish the alternative effects of embodied vs disembodied technological change operating into a vertically connected economy. Disembodied technological change turns out to positively affect employment dynamics in the "upstream'' sectors, while expansionary investment does so in the "downstream'' industries. Conversely, the replacement of obsolete capital vintages tends to exert a negative impact on labour demand, although this effect turns out to be statistically less robust.
Keywords: O14; O31; O33; 330; Innovation; disembodied and capital-embodied technological change; employment; job-creation; job-destruction; sectoral interdependencies